An Allosteric Metal–Organic Framework That Exhibits Multiple Pore Configurations for the Optimization of Hydrocarbon Separation. Issue 20 (22nd May 2019) - Zhou, Beibei; Zeng, Tengwu; Shi, Zhao‐Lin; Zhang, Gen; Horike, Satoshi; Zhang, Yue‐Biao
Abstract: The function of allosteric enzymes can be activated or inhibited through binding of specific effector molecules. Herein, we describe how the skeletal deformation, pore configuration, and ultimately adsorptive behavior of a dynamic metal–organic framework (MOF), (Me2 NH2 )[In(atp)]2 (in which atp=2‐aminoterephthalate), are controlled by the allocation and orientation of its counter ions triggered by the inclusion/removal of different guest molecules. The power of such allosteric control in MOFs is highlighted through the optimization of the hydrocarbon separation performance by achieving multiple pore configurations but without altering the chemical composition. Abstract : Something to pore over : Multiple pore configurations have been realized in an ionic metal–organic framework through the dynamic transformation upon various solvation/desolvation routes, in which the allocation and orientation of the counter ions in the pore act as an allosteric site in the channel for tuning the hydrocarbon separation performance (see figure).